Reliability and agreement of lumbar multifidus volume and fat fraction quantification using magnetic resonance imaging. (June 2022) - Rummens, Sofie; Bosch, Saskia; Dierckx, Sofie; Vanmechelen, Anna; Peeters, Ronald; Brumagne, Simon; Desloovere, Kaat; Peers, Koen
Abstract: Introduction: Magnetic resonance imaging (MRI) is the standard to quantify size and structure of lumbar muscles. Three-dimensional volumetric measures are expected to be more closely related to muscle function than two-dimensional measures such as cross-sectional area. Reliability and agreement of a standardized method should be established to enable the use of MRI to assess lumbar muscle characteristics. Objectives: This study investigates the intra- and inter-processor reliability for the quantification of (1) muscle volume and (2) fat fraction based on chemical shift MRI images using axial 3D-volume measurements of the lumbar multifidus in patients with low back pain. Methods: Two processors manually segmented the lumbar multifidus on the MRI scans of 18 patients with low back pain using Mevislab software following a well-defined method. Fat fraction of the segmented volume was calculated. Reliability and agreement were determined using intra-class correlation coefficients (ICC), Bland-Altman plots and calculation of the standard error of measurement (SEM) and minimal detectable change (MDC). Results: Excellent ICCs were found for both intra-processor and inter-processor analysis of lumbar multifidus volume measurement, with slightly better results for the intra-processor reliability. The SEMs for volume were lower than 4.1 cm³. Excellent reliability and agreement were also found for fat fraction measures, with ICCs of 0.985–0.998 and SEMs below 0.946%. Conclusion: The proposed method to quantify muscle volume and fat fraction of the lumbar multifidus on MRI was highly reliable, and can be used in further research on lumbar multifidus structure. Highlights: Three-dimensional volumetric measures are recommended to assess paraspinal muscle morphology. Chemical shift magnetic resonance imaging is the standard for the quantification of intramuscular fat. Description of a standardized and easily replicable method to assess lumbar multifidus volume and fat fraction. Excellent intra- and inter-processor reliability of this method.